Pathogenic variants of PROC gene caused type I activity deficiency in a familial Chinese venous thrombosis. Issue 10 (23rd July 2019) - Yue, Yongjian; Liu, Shengguo; Han, Xuemei; Xiao, Lu; Huang, Qijun; Li, Shulin; Zhuang, Kaixue; Yang, Mo; Zou, Chang; Fu, Yingyun
Abstract: Pathogenic mutation of protein C ( PROC ) gene results into the deficiency of PROC activity. This study aimed to identify the pathogenic genetic variants and to explore the functional consequence in Chinese familial venous thrombosis (VTE). Whole exome sequencing was performed to identify the pathogenic variants of anticoagulant factors. Serum coagulation and anti‐coagulation factors activity were assayed to evaluate the genetic association. Functional study of PROC antigen secretion deficiency was conducted in VTE subjects and in vitro cell lines. One rare pathogenic variant (p.Ala178Pro) was identified in the four VTE subjects but not in the normal subjects from the family. An inframeshift variant (rs199469469) was also identified in a paediatric subject of the pedigree. Further evaluation of serum PROC activity levels in p.Ala178Pro variants VTE carriers showed significantly lower PROC activity compared to non‐carriers. Furthermore, in vitro study showed that the p.Ala178Pro mutant cells had a consistent reduction in concentration of PROC antigen. In conclusions, our study demonstrated the pathogenic variant (p.Ala178Pro) contributed to PROC type I activity deficiency, which may be due to decreased secretion of PROC.